2014
DOI: 10.1007/978-3-662-44500-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic NMR Data

Abstract: An analysis of one and two-dimensional data sets using the so-called inverse Laplace transforms (ILT) and a discrete approach called Anahess is presented. Actually, the ILT is in mathematical terms an ill posed numerical inversion of Fredholm integrals with smooth kernels, meaning that several and very different solutions may fit the experimental data equally well. This inversion is referred to as an ILT in this book. The ILT and Anahess are fundamentally different methods for analysing the data, and the two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The smallest droplets appearing is likely due to an artifact that sometimes results from the inverse Laplace transformation, depending on signal-to-noise and the curve smoothing factor applied. 39 The smoothing factor has a tendency to stretch the DSD toward smaller and bigger droplets when decreased, which is not real, especially considering that the final DSD shows smaller droplets (Figure 3) than the initial DSD (Figure 2). However, there is a real possibility of small droplets appearing, because Yeung et al 40 showed that micrometer-sized droplets can detach from the surface of larger droplets when covered by high concentrations of bitumen.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The smallest droplets appearing is likely due to an artifact that sometimes results from the inverse Laplace transformation, depending on signal-to-noise and the curve smoothing factor applied. 39 The smoothing factor has a tendency to stretch the DSD toward smaller and bigger droplets when decreased, which is not real, especially considering that the final DSD shows smaller droplets (Figure 3) than the initial DSD (Figure 2). However, there is a real possibility of small droplets appearing, because Yeung et al 40 showed that micrometer-sized droplets can detach from the surface of larger droplets when covered by high concentrations of bitumen.…”
Section: Resultsmentioning
confidence: 96%
“…The DSD has a shift both towards smaller and larger droplets. The smallest droplets appearing is likely due to an artefact that sometimes results from the inverse Laplace transformation, depending on signal-to-noise and the curve smoothing factor applied 39 . The smoothing factor has a tendency to stretch the DSD towards smaller and bigger droplets when decreased, which is not real, especially considering that the final DSD shows smaller droplets (Fig 3 .) than the initial DSD (Fig.…”
Section: Effect Of Chemical 1 On Droplet Size Distributionmentioning
confidence: 99%